An Exploratory Study of Leadership Styles and the Effect on Performance Among Managers at Malaysia Airports Technologies Sdn. Bhd. - Siti Fatimah, Ashaari (2011)
Past researchers have done many studies on leadership several centuries ago. The meaning of leadership is more to organizing a group of people in order to achieve the goal. Nevertheless, researchers have still finding the perfect match on different perspective of leadership styles. This is important to measure what is the best leadership style in order to increase the performance of workers in any organizations. In addition, we could see there is still a scarcity of performance from many workers during their hours in the work place. Therefore, with the global growth happening everywhere currently, we have to deliver a good and effective leader to bring out the success of his people and accordingly to produce the effectiveness in the organization. The primary objective of this study was to explore the perceived leadership styles and the commitment of work performance among managers in the studied organization; Malaysia Airports Technologies Sdn. Bhd. The study has been done is to achieve certain objectives. Firstly, to identify whether there is any relationship between transformational leadership styles employed by the supervisor and the effect on managers' job performance. Secondly, to identify whether there is any relationship between transactional leadership styles employed by the supervisor and the effect on managers' job performance. Thirdly, to identify whether there is any relationship between passive avoidant leadership styles employed by the supervisor and the effect on managers' job performance. Lastly, to identify the most dominant leadership styles employed by the supervisor that contributed to the performance of the managers. This study is conducted on managers in the sample organization; Malaysia Airports Technologies Sdn. Bhd. Majority of respondents were around 30 - 39 ages whose having a working experience less than 3 years in the organization. About one hundred and fourteen (114)respondents have given their commitment to answer all questionnaires distributed by the researcher. Therefore, it is very hopeful that this study reveals perceived leadership styles have a significant positive relationship between managers in Malaysia Airports Technologies Sdn. Bhd. In addition, leaders could adopt innovative strategies using the suitable leadership style on them in order to produce work performance at the very best level as well as to gain the success for the long term period.